2017
DOI: 10.1002/adsc.201700843
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free O‐Arylation of Carboxylic Acid by Active Diaryliodonium(III) Intermediates Generated in situ from Iodosoarenes

Abstract: The metal-free arylative coupling of carboxylic acids using iodosoarenes without the use of a catalyst and base, which is applicable to even a highly-polar molecule bearing multiple alcohol groups, is reported. The in situ preparation of the reactive diaryliodonium(III) carboxylates is the important key to this approach, and the introduction of the trimethoxybenzene auxiliary enables both the smooth salt formations and the selective aryl transfer events during the couplings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…It was revealed that the electronic effect of the aryl rings was dominant during the reaction of p-anisyl (pyridyl) triflate 31 with phenols 32; the phenol nucleophiles selectively coupled to the electrondeficient pyridyl group to yield pyridyl ether 33 in 65-88% yield. This chemoselectivity trend has been further applied by other researchers to transfer the electron-poor aryl group of unsymmetrical iodonium salts, and it was noted that the TMP group serves as an improved dummy ligand for aryl transfer processes from heteroaryl(TMP)iodonium salts (Seidl et al, 2016;Dohi et al, 2017). In 2020, Stuart et al reported a convenient method for phenol arylation using the in-situ-generated aryl(TMP)iodonium salts 34 (Gallagher et al, 2020) (Figure 2A, Equation b).…”
Section: Heteroaryliodonium Salts As Highly Reactive Pseudo-halidesmentioning
confidence: 90%
See 1 more Smart Citation
“…It was revealed that the electronic effect of the aryl rings was dominant during the reaction of p-anisyl (pyridyl) triflate 31 with phenols 32; the phenol nucleophiles selectively coupled to the electrondeficient pyridyl group to yield pyridyl ether 33 in 65-88% yield. This chemoselectivity trend has been further applied by other researchers to transfer the electron-poor aryl group of unsymmetrical iodonium salts, and it was noted that the TMP group serves as an improved dummy ligand for aryl transfer processes from heteroaryl(TMP)iodonium salts (Seidl et al, 2016;Dohi et al, 2017). In 2020, Stuart et al reported a convenient method for phenol arylation using the in-situ-generated aryl(TMP)iodonium salts 34 (Gallagher et al, 2020) (Figure 2A, Equation b).…”
Section: Heteroaryliodonium Salts As Highly Reactive Pseudo-halidesmentioning
confidence: 90%
“…This Cu(I)-catalyzed synthesis of diaryl ethers using diaryliodonium salts is a complementary strategy to the previously mentioned metal-free arylation of phenols. The arylation of oxygen nucleophiles using heteroaryliodonium salts was not limited to the preparation of aryl(heteroaryl) ethers; as in the cases of other oxygen nucleophiles, it was demonstrated that benzoic acid was also arylated to produce quinolin-3-yl benzoate via the in-situ-generated iodonium salt bearing a 3quinolyl group (Dohi et al, 2017). Further, the chemistry of cyclic iodonium salts has recently experienced growing development (Chatterjee and Goswami, 2017).…”
Section: Heteroaryliodonium Salts As Highly Reactive Pseudo-halidesmentioning
confidence: 99%
“…As they said, this effect was attributed to counterion activation of diaryliodonium salts. Kita and Dong dependently reported the PhIO‐mediated C−O couplings (Scheme ).…”
Section: Acids As Nucleophiliesmentioning
confidence: 99%
“…Recently, facile direct esterification of carboxylic acids, representing a largely untapped branch of ester bond formation, has received intense attention . Among the reactions, significant contributions by Olofsson, Zhang and others have established the cross coupling of carboxylic acids with diaryliodonium salts. Additionally, utilization of the copper catalysts in the oxidative coupling of carboxylic acids with boronic acids, known as the Chan‐Lam reaction, has provided an attractive way to access ester‐containing products (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%